Teaching and Learning in COVID-19 Lockdown in Scotland: Teachers’ Engaged Pedagogy - Colville, Tracey; Hulme, Sarah; Kerr, Claire; Mercieca, Daniela; Mercieca, Duncan P. (Frontiers in Psychology, 2021)
This paper reports on a study of teachers’ perceptions of teaching and learning in Scotland during the COVID-19 pandemic through the lens of engaged pedagogy and the ideas of bel hooks. It aimed to explore the different ways that teachers experienced teaching and learning during this time and the impact this may have had on teacher identity. 60 teachers and head teachers were interviewed using MS Teams in the period April-June, 2020. For this paper, 18 transcripts were analysed by members of the research team. Four key themes emerged from the interview data: Working from home, parental engagement, teacher identity, and changes in pedagogy. Each of these themes were discussed in terms of concepts such as engaged pedagogy, agency, self-actualization, recognition and boundary transgression situated in the work of bel hooks. The idea of boundaries wove itself throughout our data as teachers expressed how the transgression of boundaries was occurring in multiple, and often contradictory, ways in pedagogical, professional, institutional and personal spaces and systems. We see in our data evidence of a shift in practice not just in the way teachers are ‘doing’ education but also, perhaps, in the way that teachers are ‘being’ as educators as they adapt to different ways of knowing. This study provides a unique exploration of a time and space in Scotland during 2020. However, the themes and understandings that emerged are of relevance to educators internationally. Schools across the world were impacted by various lockdowns imposed by the Covid-19 pandemic and teachers faced a common set of challenges that were resolved via re-negotiation and recognition of individual and collective agency to create new pedagogies.